2022
DOI: 10.1136/bmjopen-2021-055678
|View full text |Cite
|
Sign up to set email alerts
|

Role of COVID-19 pandemic in the academic life and well-being of private sector university students: an exploratory qualitative study

Abstract: ObjectiveThe advent of the COVID-19 pandemic has caused a drastic impact on students’ life, causing physical and emotional sufferings. Considering the relevance of unprecedented conditions, we explored perceptions and attitudes of students towards their academic life and well-being amid the COVID-19 pandemic.SettingWe conducted an exploratory qualitative study using a purposive sampling approach conducted at a single-centre private nursing institution in Karachi, Pakistan.ParticipantsThe current study used in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, when students believe their academic studies will benefit their future, they are extrinsically motivated to achieve their goals (Deci & Ryan, 2012;Phalet et al, 2004), which somewhat justifies the present results. Similarly, previous studies have shown that students' low expectations for the future increase their level of amotivation and decrease their interest in school and lessons (Aydın & İşlek, 2021), while high expectations for the future and having a positive outlook towards the future decrease their level of amotivation (Akbaşlı et al, 2017;Ali et al, 2022). Consequently, the current findings suggest that positive future expectations play a positive role in supporting young people's intrinsic and extrinsic motivation and reducing their amotivation during the Covid-19, which entails various disadvantages, challenges, and risks.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, when students believe their academic studies will benefit their future, they are extrinsically motivated to achieve their goals (Deci & Ryan, 2012;Phalet et al, 2004), which somewhat justifies the present results. Similarly, previous studies have shown that students' low expectations for the future increase their level of amotivation and decrease their interest in school and lessons (Aydın & İşlek, 2021), while high expectations for the future and having a positive outlook towards the future decrease their level of amotivation (Akbaşlı et al, 2017;Ali et al, 2022). Consequently, the current findings suggest that positive future expectations play a positive role in supporting young people's intrinsic and extrinsic motivation and reducing their amotivation during the Covid-19, which entails various disadvantages, challenges, and risks.…”
Section: Discussionmentioning
confidence: 76%
“…In this direction, motivation has been reported to play an important role in students' online learning behaviors (Malinauskus & Pozerience, 2020). In another study, it was found that students' increasing anxiety about the future in this process negatively affected their motivation, which was the basis for their studies in line with their future goals (Ali et al, 2022). Therefore, this study aims to investigate the variables that predict academic motivation (intrinsic and extrinsic) and amotivation of college students during the Covid-19 pandemic process, which can provide insightful results for more efficient design of educational and training processes in times of crisis.…”
Section: Introductionmentioning
confidence: 99%
“…This supported by previous research, it has been determined that some students have expressed their frustration and distress about a non-conductive learning environment at home that has negatively impacted their academic performance during online learning. They have to deal with issues like an inadequate home environment and many distractions, which raises the stress level of the students (Ali et al, 2022).…”
Section: Non-conducive Learning Environmentmentioning
confidence: 99%